The usage of marketing approaches in the activities management of Ukrainian higher educational institutions - Romanovskyi, Оleksandr; Strashynska, Larysa; Bevzo, Halyna (My University, 2019)
The main tasks and priorities of higher education development at the present stage of development are considered and the necessity of using marketing approaches in the management of higher education institutions (HEIs) is substantiated. The main means of marketing communications of the HEIsare analyzed and the priorities of the use of exhibition events are determined, which provides the possibility of personal contact with future consumers of educational services. Розглянуто основні завдання та пріоритети розвитку вищої освіти на сучасному етапі розвитку та обґрунтовано необхідність використання маркетингових підходів в управлінні діяльністю закладів вищої освіти (ЗВО). Проаналізовано основні засоби маркетингових комунікацій ЗВО та визначено пріоритети використання виставкових заходів, що забезпечує можливість особистого контакту із майбутніми споживачами освітніх послуг.
Keywords: кафедра маркетингу; state standards; higher education institution; marketing communications; exhibition activity; market of educational services; management of educational institutions; quality of education; якість освіти; заклад вищої освіти; маркетингові комунікації; виставкова діяльність; ринок освітніх послуг; управління освітніми закладами; державні стандарти